2020
DOI: 10.1590/1678-7757-2019-0355
|View full text |Cite
|
Sign up to set email alerts
|

Tongue function and swallowing in individuals with temporomandibular disorders

Abstract: Tongue function and swallowing in individuals with temporomandibular disordersThe tongue participates in the oral phase of swallowing by pushing the food bolus toward the oropharynx. This relationship between tongue function and swallowing is little addressed addressed in individuals with temporomandibular dysfunction (TMD). Objective: To analyze the association of functional tongue conditions on swallowing in individuals with TMD.Methodology: After approval by the Institutional Review Board, the study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…The previous studies indicated a crucial role of tongue pressure or MTP in swallowing [24][25][26][27]. The key role of tongue-lip motor function in swallowing was suggested in several studies [28,29] and the studies also showed the prevalence of the elderly people who showed declined swallowing function and lower ODK [30][31][32]. Regarding tongue-lip motor function (ODK), clear evidence for the association of ODK with swallowing function is still insufficient, because there have been few studies that evaluated swallowing function using three of tongue-lip motor functions proposed by Minakuchi et al On this point, this study demonstrated the significance of motor function of posterior region of tongue (ODK /ka/) as a result of three kinds of ODK evaluations.…”
Section: Discussionmentioning
confidence: 97%
“…The previous studies indicated a crucial role of tongue pressure or MTP in swallowing [24][25][26][27]. The key role of tongue-lip motor function in swallowing was suggested in several studies [28,29] and the studies also showed the prevalence of the elderly people who showed declined swallowing function and lower ODK [30][31][32]. Regarding tongue-lip motor function (ODK), clear evidence for the association of ODK with swallowing function is still insufficient, because there have been few studies that evaluated swallowing function using three of tongue-lip motor functions proposed by Minakuchi et al On this point, this study demonstrated the significance of motor function of posterior region of tongue (ODK /ka/) as a result of three kinds of ODK evaluations.…”
Section: Discussionmentioning
confidence: 97%
“…Some researchers have hypothesized that patients with chronic TMD have irregular or weak tongue functions [14][15][16][17]. In another study, it was shown that the genioglossus muscle, which is closely related to oral functions such as chewing and swallowing, moved in coordination with and as a functional connection to digastric muscles, which function in TMJ elevation [32].…”
Section: Discussionmentioning
confidence: 99%
“…A few comparative studies investigated patients with OD problems accompanying TMD, by evaluation of correlation within the groups or with a healthy control group [14][15][16][17]. No study could be found in the literature that has investigated the differences between TMD patients with and without OD problems.…”
Section: Introductionmentioning
confidence: 99%
“…The cervical tract and the head in the presence of alterations in the flexion-extension capacity (as in the example of whiplash) can negatively affect the movement of the temporomandibular joint; mandibular dysfunction alters the position and function of the tongue [11,18,35]. The same body posture affects the ability of the tongue to generate sufficient pressure for adequate swallowing; the latter action is also influenced by the movement of the jaw and the hyoid bone in a perfect muscular-articular balance of the stomatognathic and craniocervical system [21,36,37]. A dysfunctional muscular area can cause local or distant dysfunction ("vicious cycle theory"), and consequently, a lingual complex with functional limits can cause somatic symptoms of the cervical tract through the muscular connections of the oropharyngeal, cervicomandibular, and thoracic-hyoid tract [11,18,38,39].…”
Section: The Biomechanical-structural Model and The Tonguementioning
confidence: 99%